Pretreatment of Oil Palm Empty Fruit Bunch (OPEFB) at Bench-Scale High Temperature-Pressure Steam Reactor for Enhancement of Enzymatic Saccharification - Sari, Fahriya Puspita; Falah, Faizatul; Anita, Sita Heris; Ramadhan, Kharisma Panji; Laksana, Raden Permana Budi; Fatriasari, Widya; Hermiati, Euis (International Journal of Renewable Energy Development, 2021)
Upscaling of biomass pretreatment from laboratory scale to a bench-scale reactor is one of the important steps in the application of the pretreatment for pilot or commercial scale. This study reports the optimization of pretreatment conditions, namely reaction temperature and time, by one factor at a time (OFAT) method for the enhancement of enzymatic saccharification of oil palm empty fruit bunch (OPEFB). OPEFB was pretreated using high temperature-pressure steam reactor with different reaction temperatures (160, 170, 180, 190, 200 °C) and times (10, 20, 30, 40, 50 min). The effectiveness of the pretreatment was determined based on chemical compositions of raw OPEFB and OPEFB pulp and sugar production from enzymatic saccharification of the OPEFB pulp.  Solubilized components from OPEFB, such as glucose, xylose, formic acid, acetic acid, 5-hydroxymethyl furfural (HMF), and furfural in the hydrolysate that generated during steam pretreatment were also determined. Pretreatment at 180°C for 20 min provides the highest sugar yields (97.30% of glucose yield per initial cellulose and 88.86% of xylose yield per initial hemicellulose). At the optimum condition, 34.9% of lignin and 30.75% of hemicellulose are successfully removed from the OPEFB and resulted in 3.43 delignification selectivity. The relationship between severity factor and by-products generated and the sugars obtained after enzymatic saccharification are discussed. The pulp of OPEFB at the optimum condition was also characterized for its morphological characteristic by scanning electron microscopy (SEM) and crystallinity by X-ray diffractometry (XRD).  These pulp characteristics are then compared with those of the raw OPEFB. The steam pretreatment causes some fiber disruptions with more defined and opened structures and increases the crystallinity index (CrI) by 2.9% compared to the raw OPEFB.